Prospects for the use of ultrasonic disintegrate C. xerosis for the growth of microbial cells of bacterial - Isaenko, Helen; Babych, Evgen; Bilozersky, Volodymir (Annals of Mechnikov's Institute, 2022)
Introduction. Modern comprehensive use of ultrasound remains relevant. Promising its use is known in medicine, pharmacy, industrial production for the manufacture of therapeutic and prophylactic, immunocorrective and other pharmacological agents, as well as in research and development, experimental studies to obtain disintegrates and derivatives of microorganisms. In the available literature, the use of ultrasonic disintegrates of corynebacteria for the growth of bacterial microbial cells, we have not met. The aim of this work was to study the effect of disintegrates of corynebacterial on individual members of the human normobiocenosis to determine the criteria for predicting the development of normal microflora, which helps prevent diseases caused by the violation of biocenoses. Materials and methods. Ultrasonic disintegrate was obtained by irradiating a suspension of Corynebacterium xerosis with a concentration of 10,0 McFarland units using a generator G3–109 (frequency 40.0 kHz, excitation amplitude U = 15 V, load 5 W, power 0,25 W). It was then concentrated (at 56 ± 1 ° C for 1 hour), kept at 80 ± 1 ° C for 1 hour and used to grow Lactobacillus rhamnosus or Enterococcus faecium. For this purpose, bacterial suspensions with an optical density of 1,0 units on the McF scale were added to the ultrasonic disintegrate of C. xerosis (experiment), nutrient broth with 1% glucose solution (positive control) and 0,9 % sodium chloride solution (negative control), cultured at a temperature of 37 ± 1 ° C. The study of viable cells of microorganisms before and after the growth of microbial mass of representatives (L. rhamnosus or E. faecium) in ultrasonic disintegrates of corynebacteria was performed quantitatively by determining the number of colony-forming units (CFU) per unit volume of test material (lg CFU / ml). Results & discussion. As a result of growing microbial cells of L. rhamnosus in ultrasonic disintegrates of C. xerosis there was an increase in the bacterial mass of selected bacteria from lg 7,3 ± 0,4 CFU / ml to lg 8,6 ± 0,3 CFU / ml (p = 0,01). When culturing E. faecium in disintegrates of C. xerosis, there was also an increase in enterococcal biomass from lg ͠7,0 CFU / ml to lg 9,5 CFU / ml (p < 0,05). When comparing the studied media, in particular nutrient broth with 1% glucose solution and ultrasonic disintegrate of C. xerosis, the increase in biomass of enterococcal microbial cells, a probable difference between them was not found (p = 0,05), indicating their equal suitability for growing investigated strain of Enterococcus. Instead, more favorable conditions for culturing Lactobacillus in nutrient broth with 1% glucose solution than in disintegrate of C. xerosis (p = 0,03) were found. Conclusion. The experimental study proved the successful interaction of derivatives of some bacteria with other microorganisms, as well as the importance and prospects of the presented data on the possibility of further determining the criteria for predicting the development of certain representatives of the normobiocenosis and predicting human pathology, including prevention of diseases caused by biocenoses. Keywords: derivatives of bacteria, biocenosis, normal microflora, disease warning, disintegrates.